Pain Management in Blast Crisis Phase of Chronic Myeloid Leukemia: A Case Report - Soerodjotanojo, Simson Samuel; Michael Humianto; I Putu Pramana Suarjaya; Made Septyana Parama Adi (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2024)
Background: Chronic myeloid leukemia (CML) is a slow-growing type of cancer that begins in the bone marrow's blood-forming cells and is caused by a chromosomal mutation that is assumed to develop spontaneously. As CML advances into the rapid or blast phase, it can cause significant pain. This study aimed to describe pain management in the blast crisis (BC) phase of CML. Case presentation: A 48-year-old female diagnosed with CML in the BC phase complained of severe pain in the head, shoulders, back, and tailbone area with a numeric rating scale (NRS) of 9/10. The patient received multimodal analgesic therapy with continuous IV fentanyl at a rate of 0.25 mcg/kg/hour and ketamine at 1.3 mcg/kg/minute for 24 hours. The dosage was gradually increased through titration with a target NRS of 4/10. On the fifth day, we replaced fentanyl with morphine at 0.04 mg/kg/hour and ketamine at 1.3 mcg/kg/minute, and we reduced the titration dose according to the patient’s NRS, and her pain was controlled with NRS 3-4/10 after 7 days of treatment. On the 9th day, she was discharged with oral therapy. Conclusion: Multimodal analgesia has been shown to effectively reduce the intensity of the pain in blast crisis phase.